Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fnut.2022.964484
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous vitamin C on clinical outcomes in patients with sepsis or septic shock: A meta-analysis of randomized controlled trials

Abstract: ObjectivesVitamin C deficiency is common among patients with sepsis and has been associated with poor clinical outcomes. Nevertheless, the effect of intravenous (IV) vitamin C for the treatment of sepsis remains controversial. The purpose of this meta-analysis was to evaluate the effect of IV vitamin C in patients with sepsis or septic shock.MethodsElectronic databases (PubMed, Embase, Scopus, and Cochrane Library) were searched from inception through May 25, 2022 for randomized controlled trials evaluating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
5
0
1
Order By: Relevance
“…Secondary outcomes included durations of vasopressor use and mechanical ventilation time, risk of renal replacement therapy, ICU/hospital LOS as well as changes in circulating C-reactive protein (CRP) concentration and sequential organ failure assessment (SOFA) score. Subgroup analyses were performed based on the indications of IVVC treatment and dosage of IVVC (i.e., low vs. high) with cut-off value being set at 100 mg/kg/day or 10000 mg/day as previously reported ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondary outcomes included durations of vasopressor use and mechanical ventilation time, risk of renal replacement therapy, ICU/hospital LOS as well as changes in circulating C-reactive protein (CRP) concentration and sequential organ failure assessment (SOFA) score. Subgroup analyses were performed based on the indications of IVVC treatment and dosage of IVVC (i.e., low vs. high) with cut-off value being set at 100 mg/kg/day or 10000 mg/day as previously reported ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the critically ill population receiving intravenous vitamin C (IVVC) as a monotherapy, previous meta-analyses suggested that the use of IVVC may reduce the risk of mortality without a positive impact on the length of stay (LOS) in hospital or intensive care unit (ICU) ( 16 , 17 ). However, the inclusion of a limited number of patients for analysis in the two meta-analyses [i.e., 467 patients ( 16 ) and 755 patients ( 17 )] may impair the robustness of evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mehrere Metaanalysen haben keine Reduktion der Mortalität kritisch kranker Patienten unter Vitamin-C-Gabe aufzeigen können [119,174,215]. Andere aktuelle Metaanalysen geben Hinweise auf einen möglichen dosisabhängigen Effekt von Vitamin C. In den Subgruppen der hochdosierten Gabe von Vitamin C (6-25 g/Tag) haben sich signifikante Assoziationen zu einer verminderten Mortalität gezeigt [61,156,225]. In weiteren systematischen Übersichtsarbeiten ergaben sich unter Vitamin-C-Supplementation Hinweise auf eine Verbesserung des Sequential Organ Failure Assessment (SOFA) Score sowie Assoziationen zu einem Rückgang der erforderlichen Dosis an Vasopressoren, ohne Einfluss auf die Mortalität der Patienten [13,66,172,222].…”
Section: Vitamin Cunclassified